Penerapan Konsep Sosial Sustainability pada Pola Aktivitas Pelelangan Ikan dan Ruang Publik di Kecamatan Ujung Pangkah Kabupaten Gresik (Selasar, 2022)
The potential of fish resources in Gresik district which is abundant at this time, has not been managed optimally. The existence of the processing business of milkfish farmers is still limited, in small industries to meet the needs of the local market, fisheries centers located in Ujung Pangkah Subdistrict are also considered to be inadequate by only having a container of Fish Auction Places (TPI) which is still lacking. It is hoped that the redesign of the TPI Building and Public Spaces in Ujung Pangkah Subdistrict will be able to accommodate the harvest of fish farmers and also provide public space facilities that can be utilized in Ujung Pangkah Subdistrict, Gresik Regency. contribute to the economic progress of the surrounding region. The Fish Auction Building in Ujung Pangkah Subdistrict was designed according to the food industry standards that pay attention to the level of cleanliness, safety and pollution of waste produced from fish that will be sold by fishermen. These standards serve to ensure the safety of product results from contamination. So that later the production can have a high selling price value and is safe for consumption.